Politiche di inclusione nelle aree fragili: i migranti e l’approccio territoriale della Strategia Nazionale per le Aree Interne - Giovanni Carrosio; Veronica Lo Presti (Culture e Studi del Sociale)
The theoretical reflection on development policies, at national and international level, has focused attention on the need to identify new strategies for social inclusion able to promote local development by putting in the center the quality of life and the rights of citizenship. This is all the more valid in the rural and marginal areas of our country, where the lack of access to essential resources and services and the distance from the central poles of supplying basic services are a strong limit to the wellbeing of the inhabitants and the development of their capacity for actively live and therefore promote the development of the territory. In Italy, internal areas are historically affected by migratory routes and the rooting of a new population is the lever through which to combat depopulation. The substantial presence of the population with non-Italian citizens reveals some exogenous criticalities of the new ap-proaches (resident foreigners are not citizens with full rights), but can constitute a potential for regenerating the identity and economies of the internal areas, if the policies public au-thorities are able to include and activate the skills of this portion of the population according to a model of sustainable local development.